2015
DOI: 10.5539/ijps.v7n4p19
|View full text |Cite
|
Sign up to set email alerts
|

EFL Saudi Students’ Class Emotions and Their Contributions to Their English Achievement at Taif University

Abstract: This paper investigates class academic emotions of anger, anxiety, enjoyment, hope, hopelessness, pride, boredom and shame in the academic situation and their contributions to Saudi EFL students' English achievement. It also strives to find if there are any differences in class emotions and achievement according gender and streams (science and humanities). The sample consists of 315 (177 males & 138 females) university students. The Pekrun, Goetz, Titz and Perry (2002) class-related emotions scale was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
(40 reference statements)
1
22
0
Order By: Relevance
“…In a study sample of 315 Saudi university students (177 males and 138 females), Ismail (2015) reported that females significantly outperformed males in English achievement. Likewise, Al-Nujaidi (2003) reported that significant gender differences favoring females were found in Saudi EFL learners' performances on tests.…”
Section: Role Of Gendermentioning
confidence: 99%
“…In a study sample of 315 Saudi university students (177 males and 138 females), Ismail (2015) reported that females significantly outperformed males in English achievement. Likewise, Al-Nujaidi (2003) reported that significant gender differences favoring females were found in Saudi EFL learners' performances on tests.…”
Section: Role Of Gendermentioning
confidence: 99%
“…Considering learners' emotions, Ismail (2015) emphasized the salient function of both positive and negative emotions in their processes of learning and final achievement. Furthermore, Méndez Lopez and Pea Aguilar (2013) found that both positive and negative emotions influence foreign language learners' motivation.…”
Section: Emotions and Teaching Productive Skillsmentioning
confidence: 99%
“…For example, Taylor and Albasri (2014) research discussed that there is a dramatic increase in overseas Saudi Students in western universities. The figure of Saudi students reported before 2005 was around 5000 students that has remarkably increased to 100 thousand in 2013-2014 (Ismail, 2015). In other words, the economic prosperity in KSA, government reforms opened doors for western companies and the increase in iconic and social status of Saudi families lead to 100s of thousands of Saudis to study and live abroad.…”
Section: The Significance Of English Learning In Ksamentioning
confidence: 99%
“…Despite the ever-increasing importance of EFL education and perception of youth towards English learning, there is a scarce research found in context of FLA and EFL achievement in KSA context (Ismail, 2015). Some investigations are found in recent years due to the importance of adequate researches in this domain.…”
Section: Fla and English Achievement In Saudi Arabiamentioning
confidence: 99%